Review of Clay-Drug Hybrid Materials for Biomedical Applications: Administration Routes - Kim, Myung Hun (Clays Clay Miner, 2016)
Focus here is placed on the pharmaceutical and biomedical applications of novel clay-drug hybrid materials categorized by methods of administration. Clay minerals have been used for many years as pharmaceutical and medicinal ingredients for therapeutic purposes. A number of studies have attempted to explore clay-drug hybrid materials for biomedical applications with desired functions, such as sustained release, increased solubility, enhanced adsorption, mucoadhesion, biocompatibility, targeting, etc. The present review attempts not only to summarize the state-of-the-art of clay-drug hybrid materials and their advantages, depending on the methods of administration, but also to deal with challenges and future perspectives of clay mineral-based hybrids for biomedical applications.